Lebanon against the Backdrop of the 2011 Arab Uprisings - Fakhoury, Tamirace (2011)
Lebanon, one of the most highly politicized and divided societies in the Middle East, has watched the 2011 Arab Uprising nervously. Yet its own intricate legacy cross-communal compromise and the porous nature of its society have left it relatively unscathed. However, this could easily change.